Benson's Relaxation Technique as A Non-Pharmacological Intervention to Improve Sleep Patterns in Chronic Kidney Disease (CKD) Stage 5 Patients Undergoing Hemodialysis - Yunita Yunita; Yulyanti Yulyanti; Candra Kusuma Negara; Ricky Prawira; Ari Athiutama (GLOBAL HEALTH SCIENCE GROUP, 2025)
Sleep disturbance is one of the common complaints experienced by patients with Chronic Kidney Disease (CKD) stage V undergoing hemodialysis, which has an impact on decreasing the quality of life physically, psychologically, and socially. Non-pharmacological therapy such as the Benson relaxation technique is considered effective and safe in overcoming sleep disturbances and improving the emotional well-being of patients. This study aims to evaluate the effectiveness of the Benson relaxation technique in improving the quality of life of patients with CKD stage V. The research design used was a quasi-experimental with a pre-test and post-test approach with a control group, involving 60 respondents who were divided into intervention groups (n=30) and control groups (n=30) through a purposive sampling technique. The intervention was carried out for 14 days with a duration of 15–20 minutes of exercise per day. The instrument used was a quality of life (QoL) questionnaire consisting of five aspects: satisfaction with therapy, impact on life, fear of complications, social problems, and total QoL score.The Pittsburgh Sleep Quality Index (PSQI) instrument used in this study has been proven valid (r = 0.412–0.698; p < 0.05) and reliable (Cronbach's Alpha = 0.824; p = 0.000), making it suitable for measuring patient sleep quality. Data were analyzed using statistics, with Pearson validity test, Cronbach's Alpha reliability ( α = 0.824), Shapiro-Wilk normality test, and Wilcoxon and Mann-Whitney difference tests. The results showed a significant increase in the total QoL score from 2.63 ± 0.49 to 3.27 ± 0.39 (p = 0.001). All aspects of QoL also experienced a significant increase (p < 0.05), especially in the aspect of satisfaction with therapy and decreased fear of complications. Field findings also showed that patients felt calmer, could fall asleep faster, and showed increased social interaction after the intervention. The conclusion of this study is that the Benson relaxation technique is effective in improving the quality of life of CKD stage V patients and is recommended as a nursing intervention that can be applied routinely and independently in hemodialysis service practices.